2015
DOI: 10.1128/mbio.01477-15
|View full text |Cite
|
Sign up to set email alerts
|

Silica Gel for Enhanced Activity and Hypochlorite Protection of Cyanuric Acid Hydrolase in Recombinant Escherichia coli

Abstract: Chlorinated isocyanuric acids are widely used water disinfectants that generate hypochlorite, but with repeated application, they build up cyanuric acid (CYA) that must be removed to maintain disinfection. 3-Aminopropyltriethoxysilane (APTES)-treated Escherichia coli cells expressing cyanuric acid hydrolase (CAH) from Moorella thermoacetica exhibited significantly high CYA degradation rates and provided protection against enzyme inactivation by hypochlorite (chlorine). APTES coating or encapsulation of cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…The variation in size is caused by the aggregation of the silica gel particles, and contributes greatly to their inter-particle porosity. This mirrors the results found by Brahmi et al (2014) [22] for a similar size of silica gel, prepared from Algerian siliceous sands.…”
Section: Characterisation Of the Silica Gelsupporting
confidence: 91%
See 1 more Smart Citation
“…The variation in size is caused by the aggregation of the silica gel particles, and contributes greatly to their inter-particle porosity. This mirrors the results found by Brahmi et al (2014) [22] for a similar size of silica gel, prepared from Algerian siliceous sands.…”
Section: Characterisation Of the Silica Gelsupporting
confidence: 91%
“…was then dissolved in 500 ml of distilled water at 160 °C, while being stirred for 10 min, to obtain the hydrated sodium silicate [20,22]. The nal product (silica gel) was extracted after the drop wise addition of a 2M solution of hydrochloric acid at pH 3, followed by washing with distilled water to eliminate chloride ions [21,23].…”
Section: Silica Gel Preparationmentioning
confidence: 99%
“…Therefore, the contaminant flux across the penetrated bacterial membrane/capsule interface is greater than that of intact bacterial membranes in free cells. This can also explain the advantage of the polyDADMAC capsules compared to chitosan and HPVP-co-S, as the high charge density and reactivity of quaternary amines is expected to promote higher membrane disruption [44].…”
Section: Biodegradation Of Atz By the Biohybrid Lbl Capsulesmentioning
confidence: 99%
“…Yeom et al showed that CAH activity declined as a function of increasing chlorine levels in the municipal pool waters that were treated (89). A recent study showed that properly prepared 3-aminopropyltriethoxysilane (APTES)-encapsulated cells could withstand hypochlorite concentrations up to 10 ppm, providing evidence that this could be an effective biohybrid filter medium for treating chlorinated swimming pool and other waters containing cyanuric acid (91). The APTES-encapsulated cells also showed increased permeability, allowing for degradation rates of 29 mol/min per mg of CAH protein, rivaling purified enzyme rates.…”
Section: Industrial Applications For Cahmentioning
confidence: 99%